2019
DOI: 10.1111/jnc.14871
|View full text |Cite
|
Sign up to set email alerts
|

Alpha synuclein deficiency increases CD4+ T‐cells pro‐inflammatory profile in a Nurr1‐dependent manner

Abstract: It has been suggested that extracellular alpha synuclein (αSyn) can mediate neuroinflammation in Parkinson’s disease, and that αSyn affects B‐cell maturation. However, the function of αSyn in T cells is poorly understood. We hypothesized that αSyn can affect CD4+ T‐cell proliferation and activity. We found that αSyn deficiency exacerbates disease progression in 8 weeks old C57BL6/J EAE‐induced mice, and that αSyn‐deficient CD4+ T cells have increased pro‐inflammatory response to myelin antigen relative to wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Interestingly, silencing of NR4A2 expression with siRNA downregulated IL-17 expression and upregulated the expression of IL-10, an anti-inflammatory factor. 33 Similarly, NR4A2 protected dopaminergic neurons against neuroinflammation insults by constricting the release of neurotoxic mediators by microglia, 34 while its role in regulating inflammation in ischemic stroke remains largely unknown. Therefore, our future attention may place it.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, silencing of NR4A2 expression with siRNA downregulated IL-17 expression and upregulated the expression of IL-10, an anti-inflammatory factor. 33 Similarly, NR4A2 protected dopaminergic neurons against neuroinflammation insults by constricting the release of neurotoxic mediators by microglia, 34 while its role in regulating inflammation in ischemic stroke remains largely unknown. Therefore, our future attention may place it.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent studies suggest that ɑ-syn might trigger neurodegeneration through nonamyloid mechanisms [71]. Loss of function might be of interest for explaining immune system dysregulation since previous studies have shown that in ɑ-syn knockout mice there are alterations in the maturation of T and B cells [72][73][74]. Future studies will need to further explore these alternative mechanisms.…”
Section: Discussionmentioning
confidence: 99%